Cadherins and catenins in dendrite and synapse morphogenesis - Seong, Eunju (Cell Adh Migr, 2015)
Neurons are highly polarized specialized cells. Neuronal integrity and functional roles are critically dependent on dendritic architecture and synaptic structure, function and plasticity. The cadherins are glycosylated transmembrane proteins that form cell adhesion complexes in various tissues. They are associated with a group of cytosolic proteins, the catenins. While the functional roles of the complex have been extensively investigates in non-neuronal cells, it is becoming increasingly clear that components of the complex have critical roles in regulating dendritic and synaptic architecture, function and plasticity in neurons. Consistent with these functional roles, aberrations in components of the complex have been implicated in a variety of neurodevelopmental disorders. In this review, we discuss the roles of the classical cadherins and catenins in various aspects of dendrite and synapse architecture and function and their relevance to human neurological disorders. Cadherins are glycosylated transmembrane proteins that were initially identified as Ca(2+)-dependent cell adhesion molecules. They are present on plasma membrane of a variety of cell types from primitive metazoans to humans. In the past several years, it has become clear that in addition to providing mechanical adhesion between cells, cadherins play integral roles in tissue morphogenesis and homeostasis. The cadherin family is composed of more than 100 members and classified into several subfamilies, including classical cadherins and protocadherins. Several of these cadherin family members have been implicated in various aspects of neuronal development and function.(1-3) The classical cadherins are associated with a group of cytosolic proteins, collectively called the catenins. While the functional roles of the cadherin-catenin cell adhesion complex have been extensively investigated in epithelial cells, it is now clear that components of the complex are well expressed in central neurons at different stages during development.(4,5) Recent exciting studies have shed some light on the functional roles of cadherins and catenins in central neurons. In this review, we will provide a brief overview of the cadherin superfamily, describe cadherin family members expressed in central neurons, cadherin-catenin complexes in central neurons and then focus on role of the cadherin-catenin complex in dendrite morphogenesis and synapse morphogenesis, function and plasticity. The final section is dedicated to discussion of the emerging list of neural disorders linked to cadherins and catenins. While the roles of cadherins and catenins have been examined in several different types of neurons, the focus of this review is their role in mammalian central neurons, particularly those of the cortex and hippocampus. Accompanying this review is a series of excellent reviews targeting the roles of cadherins and protocadherins in other aspects of neural development.